2008
DOI: 10.1038/modpathol.3801008
|View full text |Cite
|
Sign up to set email alerts
|

RT in situ PCR detection of MART-1 and TRP-2 mRNA in formalin-fixed, paraffin-embedded tissues of melanoma and nevi

Abstract: Melanoma antigen recognized by T cells 1 (MART-1) and tyrosinase-related protein-2 (TRP-2) are two useful markers for immunohistochemical detection of melanocytic tumors. However, these markers may be passively acquired (phagocytosed) rather than actively synthesized. Reverse transcriptase in situ polymerase chain reaction (RT in situ PCR) can amplify even small amounts of specific mRNA in cells and therefore confirm the cellular source of a marker. We developed a one-step RT in situ PCR procedure in which The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…This is illustrated by the generation of serological reagents such as mAb T311 to tyrosinase and mAbs A103 or M2-7C10 to Melan-A/MART-1, which revealed high congruency between molecular and immunohistochemical data 15;16;2628 . Interestingly, one of the few previous immunohistochemical studies of TRP-2 employing a polyclonal reagent revealed discrepancies between mRNA and protein expression for TRP-2 unlike Melan-A/MART-1, which was analyzed in the same study 14 . Diminished specificity is the inherent trade-off for good sensitivity for polyclonal reagents and polyclonal reagents to TRP-2 appear to be no exception.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This is illustrated by the generation of serological reagents such as mAb T311 to tyrosinase and mAbs A103 or M2-7C10 to Melan-A/MART-1, which revealed high congruency between molecular and immunohistochemical data 15;16;2628 . Interestingly, one of the few previous immunohistochemical studies of TRP-2 employing a polyclonal reagent revealed discrepancies between mRNA and protein expression for TRP-2 unlike Melan-A/MART-1, which was analyzed in the same study 14 . Diminished specificity is the inherent trade-off for good sensitivity for polyclonal reagents and polyclonal reagents to TRP-2 appear to be no exception.…”
Section: Discussionmentioning
confidence: 96%
“…Two of the studies were done on cryosections rather than on archival paraffin material 22;24 . Only one previous report assessed the presence of TRP-2 in a selected number of archival pigmented lesions 14 . All previous analyses used solely polyclonal reagents, which were rabbit derived and provided by a collaborating lab or a commercially available goat reagent 14;2224 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations